The Rise of China and India What's in it for Africa? - Goldstein, Andrea (OECD Publishing, 2006)
China's and India's strong appetite for energy and metal has boosted international prices and the volume and value of African exports. China in particular has become the main trade partner for a number of African countries providing cheap manufactured goods and reducing Africa's dependence from its traditional trading partners. Despite the push for exports, terms of trade and growth that the Asian giants provide to Africa, risks for sustainable poverty reduction are visible in higher raw material dependence and rent-seeking activities
Keywords: Development